Analysis of needs for the development of trainer sensor and transducer learning media based on Internet of Things (IoT) - Purnamawati Purnamawati; Muhammad Akil; Nuridayanti Nuridayanti (Jurnal Pendidikan Vokasi, 2021)
The purpose of this study was to analyze the needs of students and teachers in developing a learning media in the form of a trainer to support the sensor and transducer practicum process during the Covid-19 Pandemic. This type of research is quantitative research with descriptive statistical analysis techniques. Data were collected through questionnaires distributed online to 75 respondents, including productive electronic engineering and electrical engineering teachers at SMK Negeri 2 and SMK Negeri 10 Makassar and their students. In addition, there were also respondents from electronic engineering students at the two schools. This study indicates that facilities and infrastructure in schools are in the high category with a percentage of 64%. Learning conditions during the Covid-19 Pandemic based on data from respondents are in the medium category with a percentage of 67%. The level of need for IoT-based sensor trainer learning media to support distance learning at SMK Negeri 2 Makassar and SMK Negeri 10 Makassar is in the high category with a percentage of 72%. Based on this value, it can be concluded that practicum facilities are needed in the form of IoT-based sensors and transducer trainers that can be used as alternative learning during the Covid-19 Pandemic. It is hoped that the teachers can adjust learning tools according to pandemic conditions so that the implementation of the learning process can run smoothly.